Long‐term improvement in constipation‐related symptoms after Helicobacter pylori eradication therapy. Issue 1 (17th November 2021) - Murata, Masaki; Sugimoto, Mitsushige; Miyamoto, Shin'ichi; Kawai, Takashi
Abstract: Background: Helicobacter pylori eradication therapy effectively improves the abnormal bowel habits and abdominal symptoms of patients for a few months post‐treatment (PT). However, it is unclear whether the improvement in abnormal bowel habits and symptoms continues long term. Here, we investigated the association of successful H .  pylori eradication therapy with improvements in abdominal symptoms in the short‐ and long‐term PT. Materials and Methods: We evaluated the severity of constipation‐related abdominal symptoms in 287 H .  pylori ‐positive patients who underwent eradication therapy at pre‐treatment and 2 and 12 months PT using two measures: the Gastrointestinal Symptom Rating Scale (GSRS) and the Izumo scale. Results: In patients with constipation at pre‐treatment, constipation‐related symptom scores in the GSRS improved significantly from 7.91 ± 3.15 at pre‐treatment to 6.07 ± 2.75 at 2 months PT ( p  < 0.01) and 6.85 ± 3.46 at 12 months PT ( p  = 0.04). Patients with improved symptom scores at 2 months PT also experienced an improvement at 12 months PT. In contrast, patients who did not experience an improvement in constipation‐related symptoms at 2 months PT likewise did not experience an improvement at 12 months PT. Conclusions: Patients who experience an improvement at 2 months PT with H .  pylori eradication therapy continue to experience improved symptoms in the long term. Therefore, H .  pylori ‐positive patients with abnormal bowel habits should be recommended eradication therapy to prevent gastric cancer development and to alleviate abnormal bowel habits and abdominal symptoms.